The aesthetic practice of sound matter making. Ethnosemiotics under the test of techno and its collective listening - Dentico, Michele (E|C, 2023)
The aim of the paper is to investigate the intricate relationship between the actors involved in techno music events, through an ethnosemiotic gaze, with a focus to the practices of listening. The hypothesis is that there is a heuristic foundation in the study of techno music that goes beyond its “literal” sense and instead focuses on exploring its functioning through collective listening modalities, which form the basis for some musical experiences in related events. This calls for a pragmatistic approach that acknowledges the active role of the listener. Furthermore, the article emphasizes the significance of context and the relationships between human and non-human actors in the process of constructing musical meaning. Findings from interviews and ethnographic report, it highlights how is possible to describe a complex musical experience in terms of sensations and relationships with others, rather than solely focusing on the aesthetic aspects of the music itself. Lastly, the characteristics of an aesthetic paradigm capable of capturing the complexity of the collective listening experience of techno are outlined.